The Influence of Digital Marketing on Sales Results of Traditional Traders at Horas Market Pematangsiantar - Santi Rohdearni Panjaitan; Ben Setiawan Barus; Anju Bherna D. Nainggolan; Dermawan Perangin-angin (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this study is to determine whether there is an influence of digital marketing on the sales of traditional traders in the Horas market Pematangsiantar. The number of samples in this study were 98 respondents with an error rate of 10%. The sampling technique used is non-probability sampling. The sampling method used accidental sampling technique. Data collection was obtained from the results of distributing questionnaires to traditional traders of the Horas market Pematangsiantar. The research method used is a quantitative approach with questionnaires and managing data using SPSS. The analytical tools used are validity and reliability tests. Data analysis in this study used simple linear regression analysis. The results of simple linear regression analysis show that digital marketing variables have a positive and significant effect on sales results. The results of this study indicate that the higher the digital marketing it will affect the sales results of traditional traders in the Horas market Pematangsiantar.